La fin de la guerre froide : le Canada et la sécurité européenne - Donneur, André (Études internationales, 1992)
Canada's international commitments and notably its participation in NATO were essentially dictated by its attitude vis-à-vis the USSR. During the Cold War, Canada's attitude to the USSR was more flexible and conciliatory than that of most of its allies. Gorbachev's initiatives, however, left Ottawa skeptical at first. It was necessary to wait until May 1989 for the Prime Minister and the Secretary of State for External Affairs to declare their support for the reforms undertaken by Gorbachev. From 1990 on, Canada drew nearer to the USSR and even showed haste in recognizing the Baltic states and Ukraine. The large-scale pullout of Canadian troops form Europe does not call into question Canada's participation in NATO, cooperation among members of the Atlantic alliance being of cardinal importance to this country.